2021
DOI: 10.3390/jcm10245728
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Computer-Assisted Cognitive Rehabilitation and the Degree of Recovery in Patients with Traumatic Brain Injury and Stroke

Abstract: Objectives: To determine the effectiveness of computer-assisted cognitive rehabilitation and compare the patterns of cognitive function recovery occurring in both traumatic brain injury (TBI) and stroke. Methods: A total of 62 patients were finally enrolled, consisting of 30 with TBI and 32 with stroke. The patients received 30 sessions of computer-assisted cognitive rehabilitation (Comcog) five times per week. Each session lasted for 30 min. Before and immediately after cognitive rehabilitation, all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In fact, VR has been used successfully to stimulate attention processes following TBI [ 27 , 28 , 29 , 30 ]. Besides, the current literature reported that information and communication technologies and PC-based solutions, such as serious games, software-dedicated CR, VR simulations, or other computer-mediated approaches, have an enormous impact to promote the intensity and personalization of APT, using ecological and motivational tasks [ 31 , 32 ]. Among rehabilitative virtual systems, the VRRS-EVO (Khymeia, Padua, Italy) has an intuitive and simplified interface thanks to “remote touch”, which allows the immediate management of all its functions, offering an augmented feedback to the patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, VR has been used successfully to stimulate attention processes following TBI [ 27 , 28 , 29 , 30 ]. Besides, the current literature reported that information and communication technologies and PC-based solutions, such as serious games, software-dedicated CR, VR simulations, or other computer-mediated approaches, have an enormous impact to promote the intensity and personalization of APT, using ecological and motivational tasks [ 31 , 32 ]. Among rehabilitative virtual systems, the VRRS-EVO (Khymeia, Padua, Italy) has an intuitive and simplified interface thanks to “remote touch”, which allows the immediate management of all its functions, offering an augmented feedback to the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The scale assesses five items, physical limitation (scored 0 or 2), mental state (0 or 3), pharmacological treatment (0 or 2), invasive procedures (0 or 2), and risk factors (0 or 1), and therefore ranges from 0 to 10, with the higher the score, the higher the risk of falls. It was categorized into three risk levels: 0–1 (low), 2–3 (mild), and 4 or more (high) (Lefroy et al, 1992). The construct validity was assessed using factor analysis by Thompson (1984), who reported that CRBRS items reflect two dimensions of dependency: capacity for self-care and ability to walk.…”
Section: Methodsmentioning
confidence: 99%
“…Traumatic brain injuries are a major cause of disabilities among male adults younger than 45 years, whereas strokes generally appear after the age of 45 years (Castor & El Massioui, 2018). The pattern and degree of cognitive impairment recovery in patients with stroke and TBI may differ (Jung et al, 2021).…”
mentioning
confidence: 99%
“…The following have been identified as the main ones: (i) the inclusion of various aetiologies of ABI as a generalised concept, when the clinics presented by the patients may differ considerably [62]; (ii) the difficulty of knowing the influence of the different treatments that the patients in the control group may receive; (iii) the variability in the different conceptions of the construct "mental health" and its implications in the design of the protocol itself as well as in the practice on the quality of professional support that this population profile receives; (iv) due to the technical particularities of the research proposal, the therapist delivering the intervention and subsequently analysing a large part of the data is the same person, which may lead to biases in the results; (v) the heterogeneity in terms of the range of time after ABI in which the intervention takes place, as both groups have a wide range. This is because, at present, this is the first time that this type of support initiative is being provided in this region; so, patients are not screened according to the time of acquisition of the brain injury but by the importance of the current condition and their personal, occupational, social, and family issues.…”
Section: Limitationsmentioning
confidence: 99%